Self compassion dan self criticism pada mahasiswa yang gagal masuk kampus impian - Vika Amalia Azzahra; Isrida Yul Arifiana; Suroso Suroso (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract Self compassion refers to an individual’s attitude that encompasses self kindness, recognition of common humanity, and mindful awareness toward oneself. This study aimed to examine the relationship between self compassion and self criticism among students who failed to gain admission to their dream universities. The study employed a quantitative approach with a correlational research design. The sampling technique used was purposive sampling, involving 150 students who had experienced failure in entering their preferred universities. Data were analyzed using the Pearson Product Moment correlation test. The results indicated a significant negative relationship between self-compassion and self criticism among students who failed to enter their dream universities. Higher levels of self-compassion were associated with lower levels of self-criticism in coping with the experience of failure. This finding was supported by the correlation analysis, which showed a correlation coefficient of r = −0.607 with a significance value of p = 0.000 (p < 0.05), indicating that higher self-compassion is related to lower self-criticism, and vice versa. Students who are able to develop and embrace self-compassion effectively tend to reduce self-critical behaviors following experiences of academic failure. Abstrak Self compassion merupakan sikap individu yang mencakup kebaikan, pengakuan atas kesamaan kemanusiaan serta perhatian penuh terhadap diri sendiri. Penelitian ini bertujuan untuk mengetahui hubungan antara self compassion dengan self criticism pada mahasiswa yang gagal masuk kampus impian. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Teknik penentuan sampel menggunakan purposive sampling dengan jumlah sampel sebanyak 150 mahasiswa yang pernah mengalami gagal masuk kampus impian. Teknik analisis data menggunakan uji Product Moment. Hasil Penelitian ini menunjukkan bahwa terdapat hubungan negatif yang signifikan antara self compassion dengan self criticism pada mahasiswa yang gagal masuk kampus impian. Semakin tinggi self compassion yang dimiliki individu, maka semakin rendah self criticism mereka dalam menerima proses kegagalan. Hal ini berdasarkan hasil perhitungan korelasi Product Moment, yang dimana rxy = -0,607 dengan signifikansi p= 0,000 <0,05 artinya semakin tinggi self compassion maka semakin rendah self criticism dan sebaliknya semakin rendah self compassion maka semakin tinggi self criticism. Mahasiswa yang dapat menerima self compassion dengan baik maka individu dapat mengurangi adanya perilaku self criticism.